PDMS microspheres as rheological additives for PDMS-based DIW inks - Utkarsh Ramesh; Jonathan Miller; Bryce Stottelmire; James Beach; Steven Patterson; Laura Cumming; Sabrina Wells Torres; Dakota Even; Petar Dvornic; Cory Berkland (Advanced Industrial and Engineering Polymer Research)
Direct Ink Writing holds vast potential for additive manufacturing with broad material compatibility as long as appropriate rheological properties are exhibited by the material of choice. Additives are often included to attain the desired rheological properties for printing, but these same additives can yield products with undesirable mechanical properties. For example, silica fillers are used to create silicone inks appropriate for printing but yield cured structures that are too stiff. In this work, we investigate the applicability of PDMS microspheres as a rheological and thixotropic additive for PDMS based DIW inks. We utilize a facile oil-in-water emulsion method to reproducibly obtain small (∼5 μm) PDMS microspheres, which are then incorporated into PDMS-based inks. More traditional inks with fumed silica and thixotropic additive were compared with inks containing PDMS microspheres at equal volume loadings to determine whether the PDMS microspheres could impart the desired rheological properties for DIW. Inks including PDMS microspheres exhibited surprising thixotropic effects, which enabled prints with fidelity analogous to traditional ink employing silica filler, while producing mechanically softer prints.